2016
DOI: 10.1017/s0007114516001367
|View full text |Cite
|
Sign up to set email alerts
|

Commercial complementary food consumption is prospectively associated with added sugar intake in childhood

Abstract: Given that commercial complementary food (CF) can contain high levels of added sugar, a high consumption may predispose to a preference for sweet taste later in life. This study examined cross-sectional associations between commercial CF consumption and added sugar intake in infancy as well as its prospective relation to added sugar intake in pre-school and primary-school age children. In all, 288 children of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study with 3-d weighed dietary rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 47 publications
1
50
2
6
Order By: Relevance
“…Findings from these 7 cohort studies are given in groups with a higher exposure to sweet foods reported lower (22) and higher (23) preferences for sweet foods (other than those involved in exposure), and higher (25)(26)(27), lower (24,26) and no differences (21,24,26) in intakes of other sweet foods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings from these 7 cohort studies are given in groups with a higher exposure to sweet foods reported lower (22) and higher (23) preferences for sweet foods (other than those involved in exposure), and higher (25)(26)(27), lower (24,26) and no differences (21,24,26) in intakes of other sweet foods.…”
Section: Resultsmentioning
confidence: 99%
“…Of the cohort studies, 3 studies involved retrospective measures of exposure (21)(22)(23), and 4 studies used prospective methods (24)(25)(26)(27). Methodological details of these studies are given in Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations